Empowering Elderly Care with Social Robots - Babu, Arya; K., Srikanth (Recent Research Reviews Journal, 2024)
The increasing trend of global population ageing brings with it an urgent necessity for the introduction of innovative devices to enhance the standard of elderly care. In this context, social robots integrated with onboard systems have promising prospects of improving the quality of life of the elderly by assisting, various forms of entertainment, and health monitoring. The current study presents the interactive or embedded systems used in social robots focusing on elderly care. It also explains how embedded technologies help in human-robot interaction and the behavior of the robots in real-time, including making decisions and carrying out certain tasks autonomously, such as reminding patients to take their medication, assisting with movement, and providing psychological support. Furthermore, the research provides a brief overview of the challenges encountered in deploying such robots and highlights the role of embedded systems in social robotics. This study focuses on the importance of these technologies in minimizing the problems of an aging population.